Comparative Analysis of Hydrogel Polymer in Smartphone Devices : Thermal Stability Focused - Fitria Dwi Andriani; Maudy Pratiwi Novia Matovanni; Valda Ashila Dharmawan; Muhammad Zainul Fata; Ratu Zosa Marchanda; Beta Cahaya Pertiwi (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2025)
Hydrogel polymers have emerged as transformative materials in the field of flexible electronics, offering unparalleled properties such as high water content, mechanical flexibility, and tunable conductivity. This review critically examines the thermal stability of hydrogels and their applications in electronic devices, with a focus on smartphone technology. Despite their inherent susceptibility to thermal fluctuations—ranging from freezing-induced brittleness to dehydration at elevated temperatures—recent advancements have significantly enhanced their resilience. Strategies such as incorporating cryoprotectants (e.g., glycerol, ionic liquids), optimizing crosslinked networks, and balancing hydrophilic-hydrophobic interactions have proven effective in mitigating these challenges. These innovations enable hydrogels to maintain functionality in extreme environments, making them ideal for flexible sensors, energy storage devices, and touch screens. Notably, thermoresponsive hydrogels, which exhibit reversible phase transitions at critical solution temperatures, are paving the way for adaptive cooling systems and dynamic interfaces in next-generation electronics. The integration of hydrogels into electronic devices not only addresses thermal management issues but also unlocks new possibilities for wearable and biodegradable technologies. This review underscores the interdisciplinary potential of hydrogels, highlighting their role in advancing sustainable, high-performance electronic systems while identifying future research directions to overcome existing limitations.